2013
DOI: 10.1176/appi.ap.12060114
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Documentation: A Study of Case-Formulation Documentation in Letters After Outpatient Assessment

Abstract: Although case-formulation is considered an important skill by various training bodies, it seems that this is rarely translated into daily clinical practice. The authors discuss the possible reasons for this deficiency and discuss potential solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…There was diversity among the papers about the purpose of formulation, with only Korner et al and Abbas et al recommending that formulation be considered primarily for its role in engaging the patient. 8,26,36…”
Section: Resultsmentioning
confidence: 99%
“…There was diversity among the papers about the purpose of formulation, with only Korner et al and Abbas et al recommending that formulation be considered primarily for its role in engaging the patient. 8,26,36…”
Section: Resultsmentioning
confidence: 99%
“…The results of a study in the UK showed that the documentation status of 150 referral letters for new patients to psychiatric clinics was low and majority of the patient records (94%) had documentation defect in general conclusions. [ 7 ] The documentation evaluation status of 52 patients with cognitive disorders showed that 17% of the reviewed medical records had documentation defects. [ 6 ] Lotfnezhad et al .…”
Section: Discussionmentioning
confidence: 99%
“…Trainee cohorts have recognised their own deficiencies and underscored the necessity for enhanced formal instruction in formulation (Crockford et al, 2004). The near total lack of compliance among trainees in documenting formulations within admission reports in a UK institution suggest shortcomings may have lasting clinical implications (Abbas et al, 2013).…”
Section:  Educational Shortcomingsmentioning
confidence: 99%